2022
DOI: 10.3390/ijms23105678
|View full text |Cite
|
Sign up to set email alerts
|

Two B-Box Proteins, MaBBX20 and MaBBX51, Coordinate Light-Induced Anthocyanin Biosynthesis in Grape Hyacinth

Abstract: Floral colour is an important agronomic trait that influences the commercial value of ornamental plants. Anthocyanins are a class of flavonoids and confer diverse colours, and elucidating the molecular mechanisms that regulate their pigmentation could facilitate artificial manipulation of flower colour in ornamental plants. Here, we investigated the regulatory mechanism of light-induced anthocyanin biosynthesis during flower colouration in grape hyacinth (Muscari spp.). We studied the function of two B-box pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Light intensity plays a central role in obtaining energy for plants to survive [ 60 ]. Low light stress is a major abiotic stress for the grape industry and can significantly affect plant growth and development [ 61 ], especially during the rainy season. The upregulation of Vvi-MIR399b , Vvi-MIR399c , Vvi-MIR399d , Vvi-MIR399e , and Vvi-MIR399f under low light stress indicate that they might act as positive regulators of low light stress ( Figure 5 a).…”
Section: Discussionmentioning
confidence: 99%
“…Light intensity plays a central role in obtaining energy for plants to survive [ 60 ]. Low light stress is a major abiotic stress for the grape industry and can significantly affect plant growth and development [ 61 ], especially during the rainy season. The upregulation of Vvi-MIR399b , Vvi-MIR399c , Vvi-MIR399d , Vvi-MIR399e , and Vvi-MIR399f under low light stress indicate that they might act as positive regulators of low light stress ( Figure 5 a).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies on transcription factors in other species have also confirmed that transcription factors with transcriptional activation activity can also act as repressors under certain conditions. In grape hyacinth, MaBBX51 interfered with the binding of MaHY5 to the promoters of MaMybA and MaDFR , thereby inhibiting anthocyanin biosynthesis ( Zhang et al., 2022 ). VvMYB30 in grapevine competes with activator VvMYB14 to bind to common binding sites in VvSTS15/21 promoter, controls stilbene biosynthesis in grapevine ( Mu et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a member of the B-box zinc finger gene (BBX) family is a target of HY5. It is involved in the regulation of anthocyanin accumulation [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%